2020
DOI: 10.1016/s1473-3099(20)30232-2
|View full text |Cite
|
Sign up to set email alerts
|

Viral dynamics in mild and severe cases of COVID-19

Abstract: 4 Yang X, Yu Y, Xu J, et al. Clinical course and outcomes of critically ill patients with SARS-CoV-2 pneumonia in Wuhan, China: a single-centered, retrospective, observational study. Lancet Respir Med 2020; published online Feb 24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

85
1,626
18
69

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,668 publications
(1,798 citation statements)
references
References 5 publications
85
1,626
18
69
Order By: Relevance
“…Also of note, TMPRSS2 is highly expressed in the lung and kidneys, but is present in only low to moderate levels in the heart and blood vessels, suggesting other mechanisms of injury for the latter organ systems [56]. Lastly, the amount of viral load in SARS-CoV-2 infection correlates with disease severity, with higher viral loads on presentation correlating with worse disease outcomes [57]. This study highlights the potential importance of direct viral toxicity in the pathogenesis of COVID-19 infections.…”
Section: Viral Toxicity and Myocardial Injury In Covid-2mentioning
confidence: 99%
“…Also of note, TMPRSS2 is highly expressed in the lung and kidneys, but is present in only low to moderate levels in the heart and blood vessels, suggesting other mechanisms of injury for the latter organ systems [56]. Lastly, the amount of viral load in SARS-CoV-2 infection correlates with disease severity, with higher viral loads on presentation correlating with worse disease outcomes [57]. This study highlights the potential importance of direct viral toxicity in the pathogenesis of COVID-19 infections.…”
Section: Viral Toxicity and Myocardial Injury In Covid-2mentioning
confidence: 99%
“…These data are important to compare with that of the literature which shows that the viral RNA load can remain high for about three weeks in most patients in the absence of specific treatment [19,23] with extreme cases lasting for more than a month. A study conducted in 76 Chinese COVID-19 inpatients showed that high viral RNA load is associated with the severity of the disease [24]. Furthermore, in a study conducted on a small group of 16 Chinese COVID-19 inpatients, viral RNA was positively detected in 50% of them, after resolution of symptoms for a median duration of 2.5 days and a maximum of eight days [25].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is an emerging disease, these viruses cause direct and indirect transmission of respiratory diseases with a wide range of asymptomatic, cold symptoms from respiratory/fever symptoms, cough, shortness of breath to kidney failure and death, leading to more severe respiratory illness epidemic and pandemic in most countries of the world (9). The complete clinical manifestation is not clear yet and understanding of the transmission risk is incomplete (10), but the virus is believed transmitted mostly via contact, droplets, aspirates, feces, and aerosols transmission is highly possible.…”
Section: Introductionmentioning
confidence: 99%